Multi-fault rupture behavior of the 1786 M 73/4 Kangding earthquake on the eastern margin of the Tibetan Plateau - Feng, Jiahui; Chen, Lichun; Han, Mingming; Gao, Shuaipo; Li, Yanbao; Lu, Lili; Chen, Shunyun (Frontiers in Earth Science, 2023)
The 2022 Luding Ms 6.8 earthquake has drawn attention to the Xianshuihe fault zone. Historically, there was an M 73/4 earthquake in this region in 1786. Because the surface rupture of this historic earthquake was not obvious, there is still much debate over the extent of the surface rupture, which is critical for comprehending tectonic activity and assessing seismic risk for the Xianshuihe fault (XSHF). In particular, the seismogenic structure of this earthquake was connected by three active left-lateral strike-slip faults—the Anninghe fault (ANHF), Daliangshan fault (DLSF), and XSHF—where a large earthquake could cause multi-fault rupture. Given this criteria, we report the results of a series of trenches excavated in the vicinity of the epicentre at the northern section of the DLSF, the northern section of the ANHF, the Zheduotang section, and the Selaha section of the XSHF. We find that (1) three palaeoseismic events have been revealed on the northern section of the ANHF: BE1, ~1003 AD; BE2, 1000~1182 AD; and BE3, 1536 AD as M 7 earthquakes; and (2) two palaeoseismic events have occurred on the Selaha fault during the last 500 years. The first event corresponds to the AD 1725 Kangding M 7 earthquake, and the latest event may be the AD 1786 M 73/4 earthquake. (3) Three palaeoseismic events occurred on Zheduotang: ZD1, 1215 BC~315 AD; ZD2, 830 BC~705 AD; and ZD3, the 1955 AD Kangding M 71/2 earthquake. (4) The 1786 Kangding M 73/4 earthquake was probably a multi-fault rupture event, as evidenced by trenching profile evidence, nearby offset geomorphic features, and historical earthquake data. Not only did the Moxi fault, a seismogenic structure, simultaneously break during this earthquake, but so did the southern end of the Selaha fault to the north and the Shimian fault (DLSF) to the south.